Influence of Chemical Composition on the Antioxidant Activity and Toxicity of Essential Oils of Cymbopogon nardus (l.) Rendle and Eucalyptus camaldulensis dehnh Acclimatized in Benin - AGNIMONHAN, Finagnon H.; ALLANTO, S. Florence; Kpadonou-Kpoviessi, Bénédicta; Dah-Nouvlessounon, Durand; AGBANI, Pierre; Atchade, Bardieu; GBAGUIDI, FERNAND; BABA-MOUSSA, LAMINE; GBENOU, Joachim; KPOVIESSI, D. S. Salomé (My University, 2022)
Essential oils (EO) of aromatic plants have always been used by humans for healing, perfume or food. But an oil using does not always give desired results. Faced with this difference in results, it would therefore be advisable to control the chemical composition in order to optimize the biological activity of each EO. This work is interested in the study of influence of the chemical composition on the antioxidant activity and the toxicity of EO of two plants cultivated in Benin. EO of fresh leaves of Cymbopogon nardus (L.) Rendle (C.n) and of Eucalyptus camaldulensis Dehnh (E.c), collected around 7 AM, 1 PM and 7 PM, are obtained by hydrodiffusion. The chemical composition evaluated by GC/FID and GC/MS varies qualitatively and quantitatively depending on the time of harvest. The main compounds identified are monoterpenes and sesquiterpenes which the rate varies. The antioxidant activity of EO tested by DPPH method also varies. The antioxidant activity of C.n EO is interesting at 1 PM (EC50 = 0.97 mg/mL) and weak at 7 AM (EC50 = 1.62 mg/mL). In contrast, that of E.c is better at 7 PM (EC50 = 6.23 mg/mL) and weak at 1 PM (EC50 = 42.64 mg/mL). This variation in oil activity could be explained not only by the variation in chemical composition but also by the presence of certain compounds recognized as antioxidants. Our oil samples tested on Artemia salina Leach larvae are less toxic (LC50 ˃ 26 µg/mL) than camptothecin (LC50 = 13.27 µg/mL), a reference compound
Keywords: Cymbopogon nardus (L.) Rendle; Eucalyptus camaldulensis Dehnh; essential oil; antioxidant activity; toxicity